Peer Group Mentoring for Teacher Development at a Brazilian Vocational Education Institute - Page de Castro, Julio; Mahlamäki-Kultanen, Seija; Luis Anjos da Silva, Adney; Maia de Almeida Bento, Rafael; Costa da Silva, Michelle; Íris da Silva Júnior, Ademário (Ammattikasvatuksen aikakauskirja, 2019)
This research aimed at piloting Peer Group Mentoring (PGM) in a Brazilian vocational education institute. The participants were both newcoming and experienced instrumental analysis (INAN) teachers in a large and networked public Brazilian Vocational Education and Training (VET) institute. Since the public vocational education system in Brazil has an expansion program underway, this pilot introduces a new method for teacher initiation and even broader institution level development. Research questions dealt with experiences and contributions from the PGM pilot. A group of ten teachers from three different campuses carried out 11 experimental workshops on five different techniques of INAN that cover the skills needed for future chemistry technicians. After each experiment, the group made a report discussing the protocol of analysis, the competences that students need to develop as well as pedagogical, logistic and toxicity issues with the help of the facilitator, the first author. This kind of common construction of INAN experimental workshop protocols was entirely new in the institute and peer-group mentoring needed to take into account the subject-specific needs and interests regarding the context. The participants’ experiences from peer-group mentoring were collected with a qualitative survey. The experiences were positive, and the participants on both sides recognized the usefulness of mixing new-coming and experienced teachers. This PGM process of teachers also contributed to improving protocols for practical classes with students and building learning environments such as chemical laboratories at one of the campuses. Based on the PGM pilot, we conclude that mixing new- comers and more experienced teachers in PGM is beneficial for both sides and can contribute to institute-level development in a Brazilian vocational institute. The PGM pilot took form and contributed to knowledge-sharing and construction, the development of curricula and teaching facilities.